Development Of A Solar Drying Unit For The Cocoa Smallholders In Malaysia - Hii, Ching Lik (2003)
Sun drying is the most popular method used by the Malaysian smallholders to dry cocoa beans during the harvesting season. However, various limitations have been associated with this traditional practice particularly due to unpredictable weather conditions. The sun dryer is usually without any means of protection in the event of rain unless labour is available to look after the dryer. In situations where no other alternatives of natural drying are available, the smallholders will either continue using the sun dryer or sell wet beans at a lower price. This study was carried out to develop a small-scale solar dryer to provide an additional option to the smallholders in cocoa drying. The concept of direct solar drying was adopted where the product is dried inside a transparent enclosure using direct sunlight. Overall dimension of the solar dryer prototype measured 1565 mm x 912 mm x 1375 mm (L x W x H). Most of the structural components were constructed using 'Chengal' hard wood. The side panels and drying platform were constructed from plywood and transparent Ultra Violet Stabilised Polyethylene film was used to form the enclosure.Air enters through the perforated platform (about 15% perforation) and the side air gaps (measuring 1365 mm x 40 mm) and the humid air exits through the apertures (measuring 159 mm x 1565 mm) at the apex. Two removable windows (measuring 1565 mm x 600 mm) were made at both sides of the dryer to facilitate loading, unloading and mixing. Individual part of the prototype was connected using bolts, nuts and screws to ease assembling and dismantling on farm. The total material cost of construction for a unit of solar dryer was RM 156.76. Quality of the dried cocoa beans was assessed in terms of acidity (pH and titratable acidity), degree of fermentation (cut test and fermentation index), surface mould, odour and sensory evaluation. The performance of the solar dryers was also assessed in terms of bean moisture content reduction, bed and air temperatures. Two trials were carried out to determine the effect of loading on solar drying and to compare between the solar dryer and sun dryer. From the studies, the solar dryer is recommended to the smallholders for 20 kg wet beans using perforated drying platform. The performance of the solar dryer and quality of the beans showed no significant difference (p>0.05) as compared to sun drying. This would be an added advantage to the smallholders as protection of the beans could be achieved through solar drying. Based on the recommendation, the solar dryer was able to produce beans with good external appearance, extremely light in surface mould, high in degree of fermentation and acceptable in terms of odour and sensory evaluations. The drying period was shorter at this loading (20 kg) which could eliminate the risk of mould growth due to prolong drying and the beans temperatures were well below the limit detrimental to the quality.